Evidence of epigenetic regulation of the tumor suppressor gene cluster flanking RASSF1 in breast cancer cell lines - Prando, Erika da Costa [UNESP]; Cavalli, Luciane Regina; Rainho, Claudia Aparecida [UNESP] (Landes Bioscience, 2011)
Epigenetic mechanisms are frequently deregulated in cancer cells and can lead to the silencing of genes with tumor suppressor activities. The isoform A of the Ras-association domain family member 1 (RASSF1A) gene is one of the most frequently silenced transcripts in human tumors; however, few studies have simultaneously investigated epigenetic abnormalities associated with the 3p21.3 tumor suppressor gene cluster flanking RASSF1 (i.e., SEMA3B, HYAL3, HYAL2, HYAL1, TUSC2, RASSF1, ZMYND10, NPRL2, TMEM115 and CACNA2D2). This study aimed to investigate the role of epigenetic changes to these genes in 17 breast cancer cell lines and in three non-tumorigenic epithelial breast cell lines (184A1, 184B5 and MCF 10A) and to evaluate the effect on gene expression of treatment with the demethylating agent 5-Aza -2'-deoxycytidine and/or Trichostatin A (TSA), a histone deacetylase inhibitor. We report that, although the RASSF1A isoform was determined to be epigenetically silenced in 15 of the 17 breast cancer cell lines, all the cell lines expressed the RASSF1C isoform. Five breast cancer cell lines overexpressed RASSF1C when compared with the normal epithelial cell line 184A1. Furthermore, the genes HYAL1 and CACNA2D2 were significantly overexpressed after the treatments. After the combined treatment, RASSF1A re-expression was accompanied by an increase in expression levels of the flanking genes. The Spearman's correlation coefficient indicated a positive co-regulation of the following gene pairs: RASSF1 and TUSC2 (r = 0.64, p = 0.002), RASSF1 and ZMYND10 (r = 0.58, p = 0.07), RASSF1 and NPRL2 (r = 0.48, p = 0.03), ZMYND10 and NPRL2 (r = 0.71; p = 0.0004) and NPRL2 and TMEM115 (r = 0.66, p = 0.001). Interestingly, the genes TUSC2, NPRL2 and TMEM115 were found to be unmethylated in each of the untreated cell lines. Chromatin immunoprecipitation using antibodies against the acetylated and trimethylated lysine 9 of histone H3 demonstrated low levels of histone methylation in these genes, which are located closest to RASSF1. These results provide evidence that epigenetic repression is involved in the downregulation of multiple genes at 3p21.3 in breast cancer cells.
Keywords: DNA methylation; histone modification; gene expression; breast cancer cell lines; tumor suppressor genes; RASSF1